Relevance of Capital Structure Theories in the Service Sector - Szemán, Judit (Theory, Methodology, Practice – Review of Business and Management, 2017)
The aim of this study is to examine the relevance of capital structure theories in the Hungarian service sector between 2008 and 2014. The service sector stands in the centre of research, as the role of this sector is becoming more and more important. Whereas the importance of other sectors has decreased in the previous years and decades, the role of services shows an increasing trend in developed societies. The paper focuses on three factors. Firstly, I examine whether the classical theory is relevant, in which there is a negative linkage between profitability and capital leverage. Secondly, I examine the linkage between liquidity and capital leverage. Finally, I examine the principle of maturity matching, namely if firms in the service sector keep the golden rule to finance their non-current assets from non-current liabilities and equity.